1984
DOI: 10.1002/mrc.1270220911
|View full text |Cite
|
Sign up to set email alerts
|

Solvent dependence of the molecular structure of hydrogen cyanide determined by NMR of partially oriented molecules

Abstract: The chemical shifts and the direct and indirect spin-spin coupling constants of HCN have been measured in various liquid crystal solvents. The sign of the indirect coupling constant J(15NH) is fonnd to be negative. The C shift anisotropy is 334 f 20 ppm. The molecular structure apparently varies considerably with the solvent used. These solvent effects, which can be attributed to a correlation between vibration and rotation of the molecule, are corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…[7] oc is the carbon resonance frequency in angular units and A u = all -u, is the 13C chemical shielding anisotropy, 334 ppm (32). At any given temperature the value of 7 2 was taken to be the average of the values obtained from the 14N and 2~ nmr data given in Tables 1 and 2.…”
Section: (6) Deuterium Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] oc is the carbon resonance frequency in angular units and A u = all -u, is the 13C chemical shielding anisotropy, 334 ppm (32). At any given temperature the value of 7 2 was taken to be the average of the values obtained from the 14N and 2~ nmr data given in Tables 1 and 2.…”
Section: (6) Deuterium Relaxationmentioning
confidence: 99%
“…Hydrogen cyanide is a particularly attractive molecule for nmr study because there are potentially five different stable nmr active isotopes: 'H, 'H, I3C, 14N, and I5N. Another advantage of HCN is that its structure is accurately known (3,(22)(23)(24)(25)(26) and, as well, a number of spectroscopic constants such as nuclear quadrupolar couplings (8,9,(22)(23)(24)(25)(26)(27)(28)(29), nuclear spin rotation constants (22,24,26,30), and chemical shielding anisotropies (31)(32)(33)(34)(35) are available. These constants are essential in the interpretation of the nmr relaxation data.…”
Section: Introductionmentioning
confidence: 99%
“…2,14,18 In particular, even for simple model molecules with known structures such as monosubstituted methanes, acetylene, hydrogen cyanide, etc., the spread of data exceeded the standard error of individual measurements by 10-10 3 , and deviations up to 60% from independently measured values were observed. 19 Given these discrepancies, it was deemed impossible to determine unambiguously and confidently molecular structures in many liquid crystalline solvents using traditional spectral data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this reaction was carefully studied by 1 H NMR spectroscopy using 4.0 equiv TCNE in DMF-d 7 , with the result shown in Figure 1.I n this experiment, the 1 H NMR spectrum of the starting polymer, P(A-PVT)SO, was collected first (0 min). TCNE was then added to the solution and the evolution of 1 H NMR spectra with reaction time was recorded at 23°C.…”
mentioning
confidence: 99%
“…1 H and 2D NMR studies of TCNE in DMF-d 7 indicated that this peak is attributed to HCN formed from the hydrolysis of TCNE. 7 This side reaction could compete with the substitution reaction by consuming extra TCNE, and it could be prevented when an anhydrous solvent was used.…”
mentioning
confidence: 99%